Legal Protection for Fixed-Term Employment Contract Patterns based on Law No. 6 of 2023 on The Stipulation of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation - Mario, Heru; Panggabean, Mompang L (JURNAL AKTA, 2024)
Legal Protection for Fixed-Term Employment Contract Patterns based on the Law of the Republic of Indonesia Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation into Law is an interesting topic to study to provide the public with information regarding Fixed-Term Employment Contracts. This is because the sector of Fixed-Term Employment Contracts plays a very important role for workers in determining their welfare. The research method used is qualitative, with secondary legal sources utilizing normative and empirical legal research. The data obtained from the research show that both the government and society play a crucial role in shaping and supervising labor law policies. Legal protection for workers in Fixed-Term Employment Contracts must be fair and balanced between Fixed-Term and Permanent Employment Contract Workers. However, in the government's efforts to protect the workforce, there are still obstacles. It can be concluded that the regulation of Fixed-Term Employment Contracts in various laws and regulations reflects the government's ability to protect its people. These regulations must continuously be improved in accordance with the changing times, and oversight from the public is necessary as a control function to ensure that the latest regulations aim for the welfare of the people.